2016
DOI: 10.1002/adsc.201600985
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3‐Benzazepines by Metal‐Free Oxidative C–H Bond Functionalization–Ring Expansion Tandem Reaction

Abstract: A metal‐free synthesis of biologically important benzazepines is achieved through a single synthetic operation involving an oxidative C–H bond functionalization and ring expansion with diazomethanes as key reagent. This represents a new, strong methodology for the straightforward construction of the seven‐ring N‐heterocyclic structures under mild conditions using a 2,2,6,6‐tetramethylpiperidine 1‐oxyl (TEMPO) oxoammonium salt as oxidant. Moderate to good yields are achieved from simple, readily available tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…We assumed that the generation of the benzyl carbocation was relatively facile under this reaction condition; however, the rearrangement and cyclization process may require higher temperature and longer reaction time. We found that treating the diol 5 a with 20 mol% of ytterbium(III) triflate, copper(II) triflate, indium(III) triflate or lanthanum(III) triflate in nitromethane at 115°C for 5 hours provided 6 a only in 24-40% yields ( Table 2, entries [11][12][13][14]. By increasing temperature to 115°C, the reaction provided the best yield of the product 6 a in 64% yield ( [a] Unless otherwise noted, the reaction was carried out with 5 a (0.05 mmol) and Brønsted acids (0.2-1.0 equiv) in solvent (1 mL) at 50-115°C for 2-6 h. [b] Isolated yield after chromatography on silica gel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assumed that the generation of the benzyl carbocation was relatively facile under this reaction condition; however, the rearrangement and cyclization process may require higher temperature and longer reaction time. We found that treating the diol 5 a with 20 mol% of ytterbium(III) triflate, copper(II) triflate, indium(III) triflate or lanthanum(III) triflate in nitromethane at 115°C for 5 hours provided 6 a only in 24-40% yields ( Table 2, entries [11][12][13][14]. By increasing temperature to 115°C, the reaction provided the best yield of the product 6 a in 64% yield ( [a] Unless otherwise noted, the reaction was carried out with 5 a (0.05 mmol) and Brønsted acids (0.2-1.0 equiv) in solvent (1 mL) at 50-115°C for 2-6 h. [b] Isolated yield after chromatography on silica gel.…”
Section: Methodsmentioning
confidence: 99%
“…[7] The connection between C 4 and C 5 of compound 3 a via intramolecular condensation under basic conditions resulted in the formation of 2,3-dihydro-1H-3-benzazepine 2 b (Scheme 2, eq. [12] In particular, Kametani and co-workers reported an acid promoted pinacolpinacolone rearrangement of two examples of Cbz-N protected diol 3 f and 3 g, derived from laudanosine analogues in 3 steps, to afford 2,3-dihydro-1H-3-benzazepine products in 46 and 12% yields, respectively (method D). [8] The connection between C 5 and C 5a of compound 3 b was also achieved by the intramolecular Friedel-Crafts alkylation-type reaction to furnish the corresponding 2,3-dihydro-1H-3-benzazepine 2 c (Scheme 2, eq.…”
Section: Introductionmentioning
confidence: 99%
“…Benzannulated heterocycles such as benzo-fused azepines are a unique family of seven-membered azaheterocycles. 96 Studies published over the past two decades have highly expanded the information on pharmacology of benzazepines. They are widely found in numerous bioactive molecules, natural products, and pharmaceuticals.…”
Section: Synthesis Of Functionalized Benzazepines Through Reductive Aminationmentioning
confidence: 99%
“…The structure of several representatives of this group of bioactive products is shown in Figure 4. 96,97,99…”
Section: Figure 4 Representative Bioactive Substances Containing Benzazepine Moietymentioning
confidence: 99%
“…[19] A large number of synthetic routes to benzazepines and benzodiazepines have been described throughout the last decade, [20] the most used are those based on condensations, [21] cyclizations, [22] cycloadditions [23] and ring expansions. [24] All these classical strategies might be considered useful although they usually lack sustainability in their transformations.…”
Section: Introductionmentioning
confidence: 99%